Niacin‐mediated Tace activation ameliorates CMT neuropathies with focal hypermyelination. Issue 12 (31st October 2016) - Bolino, Alessandra; Piguet, Françoise; Alberizzi, Valeria; Pellegatta, Marta; Rivellini, Cristina; Guerrero‐Valero, Marta; Noseda, Roberta; Brombin, Chiara; Nonis, Alessandro; D'Adamo, Patrizia; Taveggia, Carla; Previtali, Stefano Carlo
Abstract: Charcot–Marie–Tooth (CMT) neuropathies are highly heterogeneous disorders caused by mutations in more than 70 genes, with no available treatment. Thus, it is difficult to envisage a single suitable treatment for all pathogenetic mechanisms. Axonal Neuregulin 1 (Nrg1) type III drives Schwann cell myelination and determines myelin thickness by ErbB2/B3‐PI3K–Akt signaling pathway activation. Nrg1 type III is inhibited by the α‐secretase Tace, which negatively regulates PNS myelination. We hypothesized that modulation of Nrg1 levels and/or secretase activity may constitute a unifying treatment strategy for CMT neuropathies with focal hypermyelination as it could restore normal levels of myelination. Here we show that in vivo delivery of Niaspan, a FDA‐approved drug known to enhance TACE activity, efficiently rescues myelination in the Mtmr2 −/− mouse, a model of CMT4B1 with myelin outfoldings, and in the Pmp22 +/− mouse, which reproduces HNPP (hereditary neuropathy with liability to pressure palsies) with tomacula. Importantly, we also found that Niaspan reduces hypermyelination of Vim (vimentin) −/− mice, characterized by increased Nrg1 type III and Akt activation, thus corroborating the hypothesis that Niaspan treatment downregulates Nrg1 type III signaling. Synopsis: The α‐secretase TACE negatively regulates Neuregulin 1 (Nrg1) type III, a main driver of Schwann cell myelination. Enhancement of TACE activity with Niaspan/niacin reduces focal hypermyelination in Charcot–Marie–Tooth and HNPP neuropathy mouse models. Downregulation of Nrg1 type III ameliorates hypermyelination in Charcot–Marie–Tooth, HNPP neuropathy and vimentin −/− mouse models. Hypermyelination is reduced by Niaspan/niacin, via enhancement of TACE activity and consequent reduction of Nrg1. TACE is the specific target of niacin in myelin‐forming Schwann cell/DRG co‐cultures. Abstract : The α‐secretase TACE negatively regulates Neuregulin 1 (Nrg1) type III, a main driver of Schwann cell myelination. Enhancement of TACE activity with Niaspan/niacin reduces focal hypermyelination in Charcot–Marie–Tooth and HNPP neuropathy mouse models.